Isolation of tyrosine-O-sulfate by Pronase hydrolysis from fibronectin secreted by Fujinami sarcoma virus-infected rat fibroblasts. - Liu, M C (1985)
In a recent paper, we reported the loss of large amounts of protein-bound tyrosine sulfate after infection of rat fibroblasts by avian sarcoma viruses. The analogy to the reported loss of surface fibronectin on malignant transformation, which contained sulfate of unknown location, called our attention to this compound. In a previous paper, we briefly reported on isolation from the supernatant fraction of rat fibroblasts infected by Fujinami sarcoma virus fibronectin that yielded tyrosine-O-sulfate on Pronase hydrolysis. In this paper, we confirm and enlarge on this observation. Highly purified fibronectin was obtained from the supernatant fraction secreted by Fujinami sarcoma virus infected rat fibroblasts that contained 1.52 residues of sulfated tyrosine per protein molecule after exhaustive Pronase hydrolysis. Assuming some loss during work up, this probably indicates 2 residues of the tyrosine sulfated per fibronectin molecule.